Evaluation on Moisture Content of Eucheuma cottonii Seaweed Variety using Statistical Quality Control Approach - Darmawan, Armin; Hambali, Mulyadi; Salam, Awal Rakhmat (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractQuality is a crucial factor of an industry. PT XYZ is an exporter and distributor company of seaweed in Makassar city. It exports various varieties of seaweed, one of them is Eucheuma cottonii. Quality must be maintained to preserve and increase company image or reputation and consumer satisfaction. The study aims to improve quality of seaweed through quality control by using Statistical Quality Control (SQC) method. Receiving data of Eucheuma cottonii seaweed obtained from 30 sample groups, each group contains three different samples. Analysis on the process capability then was carried out so that the obtained score of process capability ratio was 0.35<1 and the process capability index score was -0.12<0. It can be concluded that the receiving process of seaweed in this company was incapable and need improvement to increase receiving process capability of seaweed. Several factors caused this incapable process were the unskilled human resources on seaweed handling in material receiving process and during distribution process from the farmer, the limitation of reliable measuring instruments, and the lack of constructive partnership between farmers, suppliers, and industry. Hence, this study suggested to improve skills of the employee, supplier, and farmer regarding seaweed cultivation and handling, to provide more reliable measuring instruments, and to develop constructive partnership development among farmer, supplier, and industry as an improvement of seaweed quality on receiving process.Keywords: Statistical Quality Control, quality control, Euchema cottonii, seaweed AbstrakKualitas merupakan faktor penting dalam suatu industri. PT XYZ merupakan perusahaan eksportir dan distributor rumput laut di Kota Makassar yang mengekspor berbagai macam jenis rumput laut, salah satunya jenis Eucheuma cottonii. Kualitas produk perlu dijaga untuk mempertahankan dan meningkatkan citra perusahaan dan kepuasan konsumen. Kajian ini bertujuan meningkatkan kualitas rumput laut melalui pengendalian kualitas dengan metode Statistical Quality Control. Data penerimaan rumput laut jenis Eucheuma cottonii diperoleh sebanyak 30 kelompok sampel dan tiap kelompok terdapat tiga sampel yang berbeda. Selanjutnya dilakukan analisis kemampuan proses agar didapatkan nilai untuk rasio kemampuan proses adalah 0,35<1, dan untuk indeks kemampuan proses adalah -0,12<0. Dari hasil perhitungan dapat disimpulkan bahwa proses penerimaan rumput laut di perusahaan ini tidak capable, sehingga perlu dilakukan perbaikan untuk meningkatkan kapabilitas proses penerimaan rumput laut. Beberapa faktor yang menyebabkan proses not capable yaitu keterbatasan pengetahuan pada sumber daya manusia terkait dengan penanganan rumput laut pada proses penerimaan material dan selama proses distribusi dari petani, keterbatasan alat ukur yang reliable, lemahnya kemitraan konstruktif antara petani, pemasok, dan industri. Kualitas rumput laut pada proses penerimaan dapat ditingkatkan dengan melakukan peningkatan pengetahuan pada pekerja, pemasok, dan petani mengenai budidaya dan penanganan rumput laut, penyediaan alat ukur yang andal, serta pengembangan kemitraan yang konstruktif antara petani, pemasok, dan industri.Kata kunci: Euchema cottonii, quality control, rumput laut, Statistical Quality Control